Charakterystyka porównawcza województw na podstawie jakości powietrza - Sej-Kolasa, Małgorzata; Zielińska, Anetta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The environmental management in Poland is achieved upon three principal levels: national, regional and local (counties and other smaller areas) The aim of the article is to present the abilities of using multidimensional comparative analyses in environmental research according to territorial sphere. As an example the quality of air in the area of counties is considered using methods of linear order with the consideration of two formula aggregations of variables: exemplary formula and unexamplary one.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 110-119